State regulation and support of entrepreneurship in conditions of macroeconomic instability ("Journal "U". Economy. Management. Finance.", 2025)
The article analyses state regulation and business support in conditions of macroeconomic instability. Four types of risks are identified: financial-resource, regulatory-operational, market-technological, and reputational-institutional. The key challenges are outlined, and solutions are proposed, including digitalisation of interactions, tax incentives, public-private partnerships (PPP), and greater transparency in fund allocation.
Keywords: state regulation; business support; macroeconomic instability; risks